Positive selection drives adaptive diversification of the 4‐coumarate: CoA ligase (4CL) gene in angiosperms. Issue 16 (23rd July 2015) - Sun, Haiyan; Guo, Kai; Feng, Shengqiu; Zou, Weihua; Li, Ying; Fan, Chunfen; Peng, Liangcai
Abstract Lignin and flavonoids play a vital role in the adaption of plants to a terrestrial environment. 4‐Coumarate: coenzyme A ligase (4CL) is a key enzyme of general phenylpropanoid metabolism which provides the precursors for both lignin and flavonoids biosynthesis. However, very little is known about how such essential enzymatic functions evolve and diversify. Here, we analyze 4CL sequence variation patterns in a phylogenetic framework to further identify the evolutionary forces that lead to functional divergence. The results reveal that lignin‐biosynthetic 4CLs are under positive selection. The majority of the positively selected sites are located in the substrate‐binding pocket and the catalytic center, indicating that nonsynonymous substitutions might contribute to the functional evolution of 4CLs for lignin biosynthesis. The evolution of 4CLs involved in flavonoid biosynthesis is constrained by purifying selection and maintains the ancestral role of the protein in response to biotic and abiotic factors. Overall, our results demonstrate that protein sequence evolution via positive selection is an important evolutionary force driving adaptive diversification in 4CL proteins in angiosperms. This diversification is associated with adaption to a terrestrial environment.